Contemporary approaches to second language acquisition - García Mayo, María del Pilar (AILA applied linguistics series, 2013)
This chapter reviews past and current contributions from event-related brain potential (ERP) research to the field of L2 processing. ERPs are able to measure cognitive brain processes at a very fine-grained temporal resolution and allow for determining when linguistic processes are occurring. The technique allows for investigations of whether L1 and L2 processing differences are mainly due to the fact that L2 processing takes longer or whether different neural procedures (as evidenced by different components being present) occur in L1 and L2 processing. Findings from studies of monolingual, bi.